Respuesta :

Step-by-step explanation:

Given

x + 2y = 4

x = 4 - 2y.......... equation 1

-4x -7y = - 9.......equation 2

Putting equation 1 in equation 2

- 4 ( 4 - 2y) - 7y = - 9

-16 + 8y - 7y = -9

y = - 9 + 16

y = 7

Now

x = 4 - 2* 7 = 8 - 7 = 1

hope this helps.

Answer:

X=-10  y=7

Step-by-step explanation:

1) in first equation subtract 2y on both sides

X=4-2y

Substitute as "x" in the second equation:

-4(4-2y)-7y=-9

-16+8y-7y=-9

-16+y=-9

Y=7

Substitute y as 7 to get x)

X=4-2(7)

X=4-14

X=-10

Hope this helps

ACCESS MORE